Creative coalitions in a fractured world: An opportunity for transformative change? - Gabriele Koehler (United Nations Research Institute for Social Development (UNRISD), 2020)
As citizens, activists and analysts, we are alarmed by ever-increasing political, social, economic and climate inequalities and intensifying obstacles vis-à-vis the promises of the United Nations' 2030 Agenda for Sustainable Development. Policy retrogression is undermining transformation towards economic, social and climate justice. The growing fractures are ultimately caused by the structures and trends of the reigning economic system, both at the national and global level, a system that can be described as "unfettered capitalism". It is splitting traditional working class and middle-class alliances, and immobilising government decisions in favour of redistribution and social justice: the social contract of democratic welfare statism is under threat. However, one also observes counter-currents of resistance. Hitherto siloed activist communities are coalescing in the form of "creative" coalitions. Anecdotal examples, collected from two countries in the global North, include movements for climate justice, refugee rights, gender justice and general civil rights. The paper discusses their commonalities, strengths and shortcomings, and asks whether these creative coalitions could counter the power of economic interests and retrogressive government policies? It argues that they need to be further analysed, using innovative research approaches. This could help identify the chances of and pathways for transformative change towards a new social contract and an eco-social welfare state.
Keywords: 330; 2030 Agenda for Sustainable Development; inequalities; climate change; eco-social welfare state; creative coalitions; intersectionality